Elucidating efficacy of biomass derived nanocomposites in water and wastewater treatment - Kirti, Saumaya; Bhandari, Vinay M.; Jena, Jyotsnarani; Bhattacharyya, Arnab S (Journal of environmental management, 2018)
In the present study, two synthesis methods of nanocomposites-one involving a mixture of biomass and the other using chemical modification were investigated to evaluate practical application of green approach in pollution control, specifically for water and wastewater treatment. Newer multifunctional superparamagnetic nanocomposites using biomaterials such as unripened fruit of Cassia fistula (Golden shower) and Aloe vera were developed as an example of green approach while chemical modification was illustrated using n-octanol. Two specific model applications were studied for the developed materials-dye removal (Methyl Blue and Congo Red) and disinfection-demonstrating antimicrobial property. To elucidate the multifunctional character, the texture, morphology and composition of the prepared bionanocomposites were studied. The surface area values were 6.2 and 9.8 m(2)/g for Aloe vera and octanol based nanocomposites while the average pore diameters were 1.79 nm and 5.7 nm respectively, indicating presence of highly developed micropores in the first material having a honeycomb shape and the later showing excellent staircase type formation with larger pores. A very high dye removal to the extent of 100% was obtained that can be attributed largely to the functionalities imparted from Cassia fistula compared to ingredients from Aloe vera and octanol. The nanomaterials could be completely separated with absolute ease by applying simple magnetic field. Also, successful application of the developed materials in disinfection, removal of E. coif, was demonstrated with a very high efficiency of over 95%. The biomass derived nanocomposites exhibit excellent pollutant removal and disinfection properties, even at very low nanoparticle content; octanol based material indicating similar to 5 times lowered cost, while the Aloe vera based bionanocomposites have potential for cost reduction to the extent of 10 times as compared to only magnetite nanoparticles, thereby highlighting techno-economical alternative in water and wastewater treatment.

Exploiting functionalities of biomass in nanocomposite development: application in dye removal and disinfection along with process intensification - Kirti, Saumaya; Bhandari, Vinay M.; Jena, Jyotsnarani; Sorokhaibam, Laxmi Gayatri; Bhattacharyya, Arnab S. (Clean Technologies and Environmental Policy, 2018)
A green synthesis of multifunctional superparamagnetic nanocomposites using the whole unripened fruit of Cassia fistula (Golden shower) with potential for removal of both cationic and anionic dyes and antimicrobial property is reported for the first time in the present work. A natural medium in the form of clarified butter was used to enhance the multifunctional character. The surface morphology, textural characteristics and composition of the prepared nanoparticles and composites were studied to understand the multifunctional nature. The dye removal was investigated for four different dyes, namely methyl blue, Congo red, rhodamine-B and auramine. Iron nanoparticles were largely effective in the removal of acidic dyes, while the magnetic nanocomposites were effective for the removal of both acidic and basic dyes which can be attributed to the functionalities imparted from Cassia fistula and clarified butter. The dye removal behavior can be significantly enhanced (similar to 50%) using process intensification-adsorption coupled with acoustic cavitation, which also indicated a reduced adsorbent loading as compared to the conventional adsorptive dye removal. The nanomaterials were completely separated from dye solution with absolute ease of separation by applying simple magnetic field. Also, the developed materials were useful in disinfection of E. coli with a high efficiency of 90% confirming significant antimicrobial property at lower concentrations.

Enhanced degradation of metformin using surface-coated vortex diodes - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical engineering and processing-process intensification, 2023)
The present work successfully demonstrates, for the first time, complete degradation of metformin using newer surface-coated vortex diode (SCVD) with copper and nickel coating to provide catalytic activity in the conventional hydrodynamic cavitation (HC) for significantly enhanced degradation efficiency. The SCVDs have dual functionality and the efficacy of catalytic cavitation reactors get enhanced using process intensifications of the type H2O2 addition, pH modification, and combined approach of HC+ pH+ H2O2 apart from the advantage of low pressure drop for the vortex flow based cavitation in vortex diode (Delta P of 1 bar). Complete, 100%, degradation of metformin (MTF) was achieved within 5 min with integration of optimized H2O2 dose and exceptionally high synergistic index value over 300, indicating extraordinary synergy for both Cu and Ni-SCVD. Acidic condition promote degradation and a complete degradation with a high 43-48% mineralization was observed using HC+ pH 4+ (1:200) H2O2 with less intermediates formation. The SCVDs reveal remarkable enhancement of similar to 9800% in per-pass degradation and 1400-3400% in cavitational yield as compared to conventional cavitation process under similar conditions. The newer SCVDs with catalytic activity can provide more cost-effective solutions for industrial and real-life applications.
Keywords: Cavitation; Oxidation; pollution; Technology; Wastewater treatment

Enhanced disinfection efficiency using Cu vortex diode for providing safe drinking water: devising newer methodologies - Dixit, Divya; Balapure, Kshama; Bhandari, Vinay M. (Environmental Quality Management, 2024)
The present research aims to refine the hydrodynamic cavitation technique with traditional knowledgebase of Ayurveda for more efficient water disinfection and that has huge potential for implementation in real life, especially for substituting the existing chlorination method for drinking water treatment. The study incorporates use of newer copper reactor configuration, employing vortex flow for generating cavitation for the disinfection of water. Elimination of model contaminant, Escherichia coli, with initial concentration of ∼105 CFU/mL of bacteria was used for the disinfection study. Copper vortex diode with a capacity of 1 m3/h was employed as a cavitating device. The cavitation using copper vortex diode gave significantly higher disinfection, over 30%, compared that with conventional vortex diode, with aluminum as material of construction, under similar conditions. Remarkably, the addition of 0.1% betel leaf oil led to an extraordinary 260-fold increase in the rate of disinfection, requiring only a single pass to achieve complete bacteria elimination. Furthermore, a notably high synergistic index of 246.96 was achieved for the process intensification approach using the Cu vortex diode. The cost was substantially reduced by approximately three times to 0.011 $/m3 using the Cu vortex diode compared to the conventional vortex diode. The developed strategy offers significantly enhanced performance, as well as a techno-economical and sustainable solution for drinking water treatment to ensure the provision of safe drinking water. Moreover, the newer methodology can have the advantage of producing no harmful carcinogenic disinfection by-products compared to chemical disinfection processes apart from sustainable alternative to chlorination.